Photosensitized INA-Labelled protein 1 (PhIL1) is novel component of the inner membrane complex and is required for Plasmodium parasite development - Saini, Ekta; Zeeshan, Mohammad; Brady, Declan; Pandey, Rajan; Kaiser, Gesine; Koreny, Ludek; Kumar, Pradeep; Thakur, Vandana; Tatiya, Shreyansh; Katris, Nicholas J.; Limenitakis, Rebecca Stanway; Kaur, Inderjeet; et al. (Nature Publishing Group, 2017)
Plasmodium parasites, the causative agents of malaria, possess a distinctive membranous structure of flattened alveolar vesicles supported by a proteinaceous network, and referred to as the inner membrane complex (IMC). The IMC has a role in actomyosin-mediated motility and host cell invasion. Here, we examine the location, protein interactome and function of PhIL1, an IMC-associated protein on the motile and invasive stages of both human and rodent parasites. We show that PhIL1 is located in the IMC in all three invasive (merozoite, ookinete-, and sporozoite) stages of development, as well as in the male gametocyte and locates both at the apical and basal ends of ookinete and sporozoite stages. Proteins interacting with PhIL1 were identified, showing that PhIL1 was bound to only some proteins present in the glideosome motor complex (GAP50, GAPM1–3) of both P. falciparum and P. berghei. Analysis of PhIL1 function using gene targeting approaches indicated that the protein is required for both asexual and sexual stages of development. In conclusion, we show that PhIL1 is required for development of all zoite stages of Plasmodium and it is part of a novel protein complex with an overall composition overlapping with but different to that of the glideosome.